Improvement of Dissolution Rate of Chlorzoxazone by Solid Dispersion Technique and Development of Buccal Patch - Jagdale, Swati; Hable, Asawaree; Chabukswar, Aniruddha; Kuchekar, Bhanudas (Journal of Applied Solution Chemistry and Modeling, 2013)
Chlorzoxazone (CLZ) is insoluble in water. Its half life is 1.1 hr, dose is 250 mg and has first pass metabolism. Formation of solid dispersions of CLZ with pluronic F127 will enhance the bioavailability of the drug. Phase-solubility studies revealed AL type of curves, indicating the ability of pluronic F127 to disperse with CLZ and significantly increase in solubility. The solid dispersions of CLZ was carried out with pluronic F127 by different methods and characterized by in vitro drug release, drug content, FTIR, DSC, XRD. All the solid dispersions showed dissolution improvement compare to pure drug. These techniques revealed distinct loss of drug crystallinity in the formulation accounting for enhancement in dissolution rate. The stability study for solid dispersions indicated, all formulations were stable. Methods showing best in vitro drug release profile were selected in further development of mucoadhesive buccal patches. A buccal patch has been developed using mucoadhesive polymers HPMC K4M and carbapol 974. The developed patches were evaluated for the physicochemical, mechanical and drug release characteristics. The optimized patches showed good mechanical and physicochemical properties to withstand environment of oral cavity. The in-vitro permeation study showed that patches could deliver drug to the oral mucosa for a period of 8 hrs. The results indicate that suitable bioadhesive buccal patches with good permeability could be prepared. The batches FH4 and FC4 showed 79.65% and 79.93% permeated through goat mucosa membrane in 8 hrs. The stability study for buccal patch revealed that all batches were stable.